STRATEGI KEAGENAN KAPAL PERINTIS - Karsafman, Tjetjep; Braningtyas, Yulinda (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2020)
Basically, a company can be measure from the human resources contained therein. Therefor, form the result of SWOT analysis in internal factor in PT Andromeda Sentral Pasifik, Semarang, found there is more strength than weakness. The dominant strength is lies in professional human resource services with score 0.72, whereas the dominant weakness lies in infrastructure or IT with score 0.18. From external factor, the opportunity has a higher score than the threat. The dominant opportunity is Indonesia geographic region with score 0.72, whereas the dominant threat is political stability and rising fuel price with score 0.18. The strategic steps that was taken by business developer is giving the excellent service in documentation, providing customer with fast, accurate, dan trustworthy information, offering the customer a complete service start from land transportation, custom clearance, and all that is needed in export and impor activity, giving attractive payment term. In addition, company also receive new employee selectively, and provide training for new employee to add his/her ability.